Knowledge, attitudes and practices of hand hygiene among parents of preschool children - A Mohamed, Nurul (Universiti Sains Islam malaysia, 2016)
Background- Infections spread easily among children in nurseries due to overcrowding and their natural intimacy. Disease transmission via skin (particularly hand) contact is preventable through proper hand hygiene and good sanitation. Parental support and involvement in developing child’s hygienic behavior are essential in promoting child’s well being. This study aimed to determine knowledge, attitudes and practices of parents on hand hygiene, related to the care of their children. Methods- This cross-sectional study involved 240 parents of preschoolers in the Klang Valley, Malaysia. Participants were given self-administered questionnaires consisting statements related to personal hand hygiene, hand hygiene practices during childcare and infections related to poor hand hygiene. Results- The mean score for knowledge of hand hygiene was 2.72(SD 0.26) out of 3.00.Meanwhile, the mean score for attitude and practice of hand hygiene were 4.56(SD 0.58) out of 5.00 and 4.36 (SD 0.65) out of 5.00 respectively. Overall results showed that majority of parents had a good understanding of hand hygiene. However, about two thirds parents did not agree on washing hands before interacting with their children. Of concern, about 76% parents are unaware of correct hand washing techniques. Conclusions- This study highlighted the need for more comprehensive educational programs to create awareness regarding the importance of hand hygiene particularly among parents and children. This is very important for prevention of communicable diseases in the community.